FACTORS INFLUENCING THE MOTIVATION OF POST-FRACTURE PATIENTS TO PERFORM EARLY MOBILIZATION IN THE DAPARTAMENT OF SURGERY HOSPITAL NACIONAL GUIDO VALADARES (HNGV) DILI IN 2023 - da Costa Fernandes, Manuel; Lidia Gomes, Cooautor; Noronha, Herminio; de Jesus Amaral, Isabel; de Jesus, Acacio; Freitas Babo, Leticia (Jurnal Syntax Fusion, 2024)
In today's era of modern globalization, there are many traffic accidents involving trauma and injuries/fractures. According to the World Health Organization, by 2022 traffic accidents will be the eighth cause of death for people aged 15 to 29 in the world. And according to the WHO in 2020 states that the incidence of fractures is increasing, disability is about 13 million people with a prevalence of 2.7%, fractures in 2019 are about 15 million with a prevalence of 3.2%, a prevalence of 3.8% due to traffic accidents. Based on WHO (2020) mortality because of accident traffic in Timor Leste reach 154 or 2.18% of all deaths. In 2023 from January until June about 119 patients with fracture which is 90 male and 29 female that have been treated in department of surgery HNGV Dili. To know the factors that influence the motivation of post-fracture patients to perform early mobilization in the department of surgery Hospital Nacional Guido Valadares (HNGV) Dili in 2023. This study used a quantitative analytic method with a cross-sectional approach using non-probability sampling techniques and Total sampling techniques with a total of 40 respondents. researcher identifies 40 fracture patients which are treated in department of surgery 60% with good family support, 52.5% with moderate pain process and another variable shows 67.5% with sufficient knowledge that influence the motivation of post-fracture patients to perform early mobilization. When analyze test with statistic Spearman Rank Correlation to X1 and Y have p value = 0,000 < 0,05 and have correlation 0.606 it’s mean have a strong influence, X2 and Y have p value = 0,001 < 0,05 and have correlation 0.488 it’s mean have a sufficient influence, X3 and Y have p value = 0,000 < 0,05 and have correlation 0.623 it’s mean have a strong influence. This research shows that the results have a strong influence between family support factor, sufficient influence between pain factor and strong influence between knowledge factor that influence the motivation of post-fracture patients to perform early mobilization in the department of surgery Hospital Nacional Guido Valadares (HNGV) Dili in 2023.